Mindfulness-Based Relapse Prevention for Substance Use Disorders A Systematic Review - Grant, Sean (RAND Corporation, 2015)
RAND researchers conducted a systematic review that synthesized evidence from randomized controlled trials of Mindfulness-Based Relapse Prevention (MBRP)-used as an adjunctive therapy or monotherapy-to provide estimates of its efficacy and safety for treating adults diagnosed with alcohol, opioid, stimulant, or cannabis use disorder.